(untitled) (Revista UTCiencia: i-ISSN: 1390-6909. e-ISSN: 2602-8263, 2025)
Lycalopex culpaeus reissii, is the largest canid in South America, one of the native species of the páramo, and is also considered a biological indicator of environmental quality. Since there is no information on this species in Ecuador, the objective was to establish the most appropriate monitoring techniques for the study of the Andean fox in the paramos of Cotopaxi province. For this, an analysis and selection of the information available on the internet (repositories, articles, books, manuals, blogs), google academic, PubMed, Web of science, where we used the inclusion criteria based on monitoring techniques for mammals, and studies ranging from 1950 to 2023, using keywords such as: “monitoring”, ‘techniques’, “direct and indirect”, “Andean fox” and “Lycalopex culpaeus”, selecting a total of 48 relevant, pertinent and reliable documents. Therefore, it was concluded that the combination of direct (line transects, capture and camera traps) and indirect monitoring techniques ( footprints, feces, refuges, bones, fur, scratches, burrows, water sources, trails) plus the use of satellite technologies are adapted to the conditions of the páramo to be used in studies on the presence, population density, movements, habits and behavior, This, in turn, contributes to decision-making on policies for the protection of the Andean fox and its environment in the province of Cotopaxi.